FAKTOR-FAKTOR YANG MEMPENGARUHI KONSENTRASI KARBONMONOKSIDA DI DALAM DARAH PARA MONTIR BENGKEL OTOMOTIF - Andi Chaeruddin (Purifikasi, 2006)
The aims of this research were to determine CO concentrations in the work place of the mechanics, in the mechanics’ blood, and the influencing factors. The measurement of CO in the work place used Kitagawa Detector Gas. The microdiffusion method was used to measure Co in the mechanics’ blood. An interview was done to obtain data on health history, smoking habits, complaints and expectation. The secondary data was used to obtain data on age, and work length of the mechanics. The results showed that the average CO level in the the mechanics work place was 11,65 ppm with SD 1,12. This value was lower than the Treshold Limited Value (TLV) of 20,00 ppm. The average CO in the mechanics blood was 7,43% COHb with SD 2,87. This value was close to the TLV of 10% COHb. However, 35% of the mechanics had CO concentration level in their bloods greater the TLV. This datum was supported by their complaints of dissyness, headache, fatigue and hothead. The regression analysis showed that the concentration level of CO was significantly influenced by age, work duration, level of CO concentration in work place, and the number cigarettes consumed.